2000
DOI: 10.1002/1096-9861(20000710)422:4<579::aid-cne7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neurotrophin and repellent sensitivities of early embryonic geniculate and trigeminal axons

Abstract: Geniculate (gustatory) and trigeminal (somatosensory) afferents take different routes to the tongue during rat embryonic development. To learn more about the mechanisms controlling neurite outgrowth and axon guidance, we are studying the roles of diffusible factors. We previously profiled the in vitro sensitivity of trigeminal axons to neurotrophins and target-derived diffusible factors and now report on these properties for geniculate axons. GDNF, BDNF, and NT-4, but not NT-3 or NGF, stimulate geniculate axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 61 publications
4
37
0
Order By: Relevance
“…Gustatory ganglia express the receptors (trkB and p75 NGFR) for BDNF (Ernfors et al 1992;Nosrat 1998). Previous studies have shown that neurite outgrowth from geniculate ganglion requires BDNF and/or NT-4 (Rochlin et al 2000). We have generated BDNF −/− xNT-4 −/− doubleknockout mice by crossbreeding single neurotrophin knockout mice in order to study the development of the peripheral gustatory system in the absence of TrkB ligands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gustatory ganglia express the receptors (trkB and p75 NGFR) for BDNF (Ernfors et al 1992;Nosrat 1998). Previous studies have shown that neurite outgrowth from geniculate ganglion requires BDNF and/or NT-4 (Rochlin et al 2000). We have generated BDNF −/− xNT-4 −/− doubleknockout mice by crossbreeding single neurotrophin knockout mice in order to study the development of the peripheral gustatory system in the absence of TrkB ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidates are glial cell-line-derived neurotrophic factor (GDNF) and neurturin found in the papillae and in the innervation of the gustatory papillae in the developing tongue (Nosrat 1998;Takeda et al 2004). GDNF has been shown to elicit extensive neurite outgrowth from the geniculate ganglion (Rochlin et al 2000). These other neurotrophic factors may support lingual somatosensory and gustatory innervation in the absence of the neurotrophins BDNF and NT-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when knocking out TrkB, 95 % of geniculate ganglion neurons were (Fritzsch et al 1997). In addition to regulating the geniculate neuron number, BDNF and NT-4 differentially regulate neurite outgrowth (Rochlin et al 2000), target innervation, and taste bud development. BDNF produced in taste epithelium is required for gustatory target innervation but NT-4 is not (Hoshino et al 2010;Ma et al 2009).…”
Section: Neurotrophins and Their Functions On Taste Systemmentioning
confidence: 99%
“…Neuronal growth factor, BDNF significantly increases regenerative neuritic robustness of outgrowth and length in cultured E12-E14 geniculate ganglion cells of rat (Rochlin et al 2000;Yamout et al 2005). Also, BDNF receptor, TrkB mRNA and protein are present in embryonic and young adult geniculate ganglion cells of rodents (e.g., Yamout et al 2005).…”
Section: Surgically-lesioned (Otocyst Ablations) Geniculate Ganglion mentioning
confidence: 99%